Poverty Mosaics: Realities and Prospects in Small-Scale Fisheries - Jentoft, Svein; Eide, Arne.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Small-scale fisheries are a major source of food and employment around the world. Yet, many small-scale fishers work in conditions that are neither safe nor secure. Millions of them are poor, and often they are socially and politically marginalized. Macro-economic and institutional mechanisms are essential to address these poverty and vulnerability problems; however, interventions at the local community level are also necessary. This requires deep understanding of what poverty means to the fishers, their families and communities; how they cope with it; and the challenges they face to increase resiliency and improve their lives for the better.   This book provides a global perspective, situating small-scale fisheries within the broad academic discourse on poverty, fisheries management and development. In-depth case studies from fifteen countries in Latin America, Europe, South and Southeast Asia, and sub-Saharan Africa, demonstrate the enormously complex ecological, economic, social, cultural and political contexts of this sector. Conclusions for policy-making, formulated as a joint statement by the authors, argue that fisheries development, poverty alleviation, and resource management must be integrated within a comprehensive governance approach that also looks beyond fisheries.   The scientific editors, Svein Jentoft and Arne Eide, are both with the Norwegian College of Fishery Science, Faculty of Biosciences, Fisheries and Economics, University of Tromsø, Norway.
Chapter 1 - Setting the Stage By Svein Jentoft and Arne Eide Introduction -- Chapter 2 - Avoiding Poverty Chapter 2 - Avoiding Poverty Distributing Wealth in Fisheries By Arne Eide, Maarten Bavinck and Jesper Raakjær --    Chapter 3 - Situating Poverty A Chain Analysis of Small-Scale Fisheries By Ratana Chuenpagdee and Svein Jentoft --  Chapter 4 - The Meaning of Poverty Conceptual Issues in Small-Scale Fisheries Research By Svein Jentoft and Georges Midré --   Chapter 5 - Living on the Margin The Poverty-Vulnerability Nexus in the Small-Scale Fisheries of Bangladesh By Mohammad Mahmudul Islam --  Chapter 6 - Occupation of Last Resort? Small-Scale Fishing in Lake Victoria, Tanzania By Paul O. Onyango --  Chapter 7 - Vanished Prosperity Poverty and Marginalization in a Small Polish Fishing Community By Boguslaw Marciniak --  Chapter 8 - More than Income Alone The Anlo-Ewe Beach Seine Fishery in Ghana By Marloes Kraan --  Chapter 9 - Wealth, Poverty and Immigration The Role of Institutions in the Fisheries of Tamil Nadu, India By Maarten Bavinck --  Chapter 10 - Addressing Vulnerability Coping Strategies of Fishing Communities in Yucatan, Mexico By Silvia Salas, Maiken Bjørkan, Felipe Bobadilla and Miguel A. Cabrera -- Chapter 11 - Through Boom and Bust Coping with Poverty in Sea Snail Fisheries on the Turkish Black Sea Coast By Ståle Knudsen and Hakan Koçak --  Chapter 12 - Community Response Decline of the Chambo in Lake Malawi’s Southeast Arm By Mafaniso Hara --  Chapter 13 - To Make a Fishing Life Community Empowerment in Small-Scale Fisheries in the Pearl Lagoon, Nicaragua By Miguel González --  Chapter 14 - Learning from the Experts Attaining Sufficiency in Small-Scale Fishing Communities in Thailand By Ratana Chuenpagdee and Kungwan Juntarashote --  Chapter 15 - Facilitating Change A Mekong Vietnamese Small-Scale Fishing Community By Kim Anh Thi Nguyen and Ola Flaaaten --  Chapter 16 - Creating Action Space Small-Scale Fisheries Policy Reform in South Africa By Moenieba Isaacs --  Chapter 17 - Building Resilience Fisheries Cooperatives in Southern Sri Lanka By Oscar Amarasinghe and Maarten Bavinck -- Chapter 18 - Moving out of Poverty Conditions for Wealth Creation in Small-Scale Fisheries in Mozambique By Ana Menezes, Arne Eide and Jesper Raakjær -- Chapter 19 - The Merits of Consensus Small-Scale Fisheries as a Livelihood Buffer in Livingston Town, Guatemala By Hector Andrade and Georges Midré --  Chapter 20 - A Better Future Prospects for Small-Scale Fishing People By Svein Jentoft, Arne Eide, Maarten Bavinck, Ratana Chuenpagdee and Jesper Raakjær --   Biographies of the PovFish Team -- Index of Keywords.                  .
Keywords: Sustainable development; Social sciences; Environmental management; Environmental law; Environmental policy; Sustainable Development; Social Sciences, general; Environmental Management; Environmental Law/Policy/Ecojustice.